1998
DOI: 10.1002/(sici)1099-0968(199809)6:3<188::aid-erv227>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of test-meal induced autonomic arousal in anorexic, bulimic and control females

Abstract: This study attempted to measure three different physiological responses to food intake in eating disordered subjects. Skin conductance level (SCL), heart rate and electroencephalogram were recorded before, during and after a test-meal in 42 females (14 anorexic inpatients, 10 bulimic outpatients and 18 control subjects). Signi®cant increase in SCL during the meal was found in anorexics only. Pre-meal SCL was lower in bulimics than in controls and anorexics. No changes were found on heart rate or electroencepha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…According to Demos [ 123 ] and Blume et al [ 124 ], oscillations in beta (β) band are linked to conscious precision, strong focus, and enhanced ability in problem-solving. We also compare our results with those described in a review paper by Blume et al [ 124 ] and the work of Leonard et al [ 125 ]. In the last paper, EEG was derived at three stages, at a 1-min resting state, “eyes open” before, during, and after a test meal.…”
Section: Discussionsupporting
confidence: 70%
“…According to Demos [ 123 ] and Blume et al [ 124 ], oscillations in beta (β) band are linked to conscious precision, strong focus, and enhanced ability in problem-solving. We also compare our results with those described in a review paper by Blume et al [ 124 ] and the work of Leonard et al [ 125 ]. In the last paper, EEG was derived at three stages, at a 1-min resting state, “eyes open” before, during, and after a test meal.…”
Section: Discussionsupporting
confidence: 70%
“…EDA has further been used in research into anorexia by Léonard, Pepinà, Bond, and Treasure (1998), who observed an increase of the SCL during the meal in anorectics, while premeal SCLs were lower in bulimics than in anorectics and controls. Female binge eaters maintained higher SCLs during exposure to and consume of food compared to controls (V€ ogele & Florin, 1997).…”
Section: Eda In Other Medical and Psychological Applicationsmentioning
confidence: 99%
“…They salivate less to food cues, 50 have lower preferences for fat-sweet substances, 51,52 eat more slowly, 53 and, when eating, have an autonomic arousal response with increased skin conductance. 54 All these findings suggest that central control of eating, particularly that involving the hedonic system, is disrupted in AN. Brain Neurochemistry in AN Anomalies in the central neurochemistry involved in the control of eating behaviour have been found in AN, but most of the work has used indirect measures.…”
Section: The Central Anatomy and Psychophysiology In Response To Foodmentioning
confidence: 99%